Synthesis, characterization and DNA binding study of silver(I) complexes with 2'-thiazolylazo aminoanisole compounds (TAAA) - Pinchaipat, Bussaba; Thaempayak, Nattawan; Chotima, Ratanon; Songsasen, Apisit (Naresuan University Journal: Science and Technology (NUJST), 2021)
Bioinorganic chemistry has been attracted for many years on the biological studies of transition metal complexes, including those based on the silver(I) ion. Since azo compounds have significant biological activity, the development of new silver(I) complexes with such compounds might be of interest. Azo dyes 2-(2'-thiazolylazo)-5-aminoanisole ( p -TAAA) and 4-(2'-thiazolylazo)-3-aminoanisole ( o -TAAA) and their silver(I) complexes; [Ag-( p -TAAA)] and [Ag-( o -TAAA)] have been prepared and characterized by elemental analysis, mass spectrometry, IR spectroscopy, 1 H and 13 C NMR spectroscopy. The results reveal structures of the synthesized complexes in which silver(I) ion have bound to two molecules of 2'-thiazolylazo aminoanisole compounds with nitrogen of azo group and sulfur of thiazole ring as donor atoms. The biological activity of such complexes was examined using calf thymus DNA (CT-DNA). The mode of DNA binding interaction was investigated by electronic absorption titration. The results indicate that the synthesized silver(I) complexes bind to CT-DNA via intercalative mode of binding with binding constants of 1.44 x 10 5 M -1 for [Ag-( p -TAAA)] and 9.77 x 10 4 M -1 for [Ag-( o -TAAA)], respectively.   Keywords: Thiazolylazo, Silver(I) complexes, DNA binding, Electronic absorption titration, Binding constants (K b )